A Bilobed Schwannoma in Roof of Orbit: A Rare Case Report - Somya Dulani; Sachin Diagavane; Seema Lele; Harshal Gaurkhede (Case Reports in Ophthalmological Medicine)
In this paper, we report a case of bilobed schwannoma, presented in the roof of orbit arising from supraorbital nerve. A 62-year male presented with a nontender mass in superior part of orbit and eccentric proptosis. Visual acuity and rest of ocular examination were normal. CT scan and MRI orbit revealed an extraconal homogenous bilobed mass, of size 3.5 to 2.5 cms in roof of orbit. Fine needle aspiration cytology was done, which was suggestive of schwannoma a peripheral nerve tumor. Successful surgical excision of intact bilobed schwannoma was done with careful separation and preservation of supraorbital nerve from which it was originated. Postoperative period was uneventful though rare, less than 1%, schwannoma can present as painless mass in the orbit and proptosis. Treatment of choice is surgical excision of intact tumor to prevent recurrence and preservation of peripheral nerve from which it arises.